Analisis terhadap Implementasi Undang-Undang Nomor 27 Tahun 2022 Tentang Perlindungan Data Pribadi di Indonesia - Sumargil Sikome; Roy Marthen Moonti (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
The rapid development of information technology has increased the collection, storage, and processing of personal data, leading to a higher risk of data breaches and misuse. To ensure the protection of personal data rights, the Indonesian Government enacted Law Number 27 of 2022 on Personal Data Protection. This study aims to analyze the implementation of Law Number 27 of 2022, examine the legal protection of personal data, and assess the roles of the government, electronic system operators, and the public in supporting its implementation. This research employs a normative legal research method using a statutory approach and a conceptual approach. The findings indicate that Law Number 27 of 2022 provides a comprehensive legal framework for personal data protection. However, its implementation is still constrained by the lack of implementing regulations, the absence of an effective supervisory institution, the low level of compliance among electronic system operators, and limited public awareness regarding personal data protection. Therefore, strengthening implementing regulations, enhancing supervisory mechanisms, and improving public education and awareness are essential to achieving effective personal data protection and ensuring legal certainty.